Precise Quantitation of the Latent HIV-1 Reservoir: Implications for Eradication Strategies - Crooks, Amanda M. (J Infect Dis, 2015)
The quantitative viral outgrowth assay (QVOA) provides a precise minimal estimate of the reservoir of resting CD4(+) T-cell infection (resting cell infection [RCI]). However, the variability of RCI over time during antiretroviral therapy (ART), relevant to assess potential effects of latency-reversing agents or other interventions, has not been fully described. We performed QVOA on resting CD4(+) T cells obtained via leukapheresis from 37 human immunodeficiency virus (HIV)–infected patients receiving stable suppressive ART for a period of 6 years. Patients who started ART during acute (n = 17) or chronic (n = 20) HIV infection were studied once HIV RNA levels were <50 copies/mL for ≥6 months. Using random effects analysis of 160 RCI measurements, we found that RCI declined significantly over time (P < .001), with an estimated mean half-life of 3.6 years (95% confidence interval, 2.3–8.1 years), remarkably consistent with findings of prior studies. There was no evidence of more rapid decay in acute versus chronic HIV infection (P = .99) for patients suppressed ≥6 months. RCI was reliably estimated with longitudinal measurements generally showing <2-fold variation from the previous measure. When QVOA is performed in this format, RCI decreases of >6-fold were rare. We suggest that a 6-fold decline is a relevant threshold to reliably identify effects of antilatency interventions on RCI.